Stevens-Johnson Syndrome following Failure of Genetic Screening prior to Carbamazepine Prescription - Suraya Ahmad Nasir; Huann Lan Tan; Hui Jan Tan; Haizal Mohd Hussaini; Roszalina Ramli (Case Reports in Dentistry)
Failure to screen susceptible individuals for human leucocyte allele B∗1502 leads to the onset of Stevens-Johnson syndrome (SJS). We report a case of a 27-year-old Malay female who was treated with carbamazepine following the diagnosis of trigeminal neuralgia without a genetic screening. She was prescribed 150 mg of carbamazepine initially and the dose was increased to 300 mg following the initial dose. A sudden development of skin and mucous membrane ulcers was observed and this warranted immediate hospitalization. A diagnosis of SJS was made and she was treated immediately with intravenous corticosteroids. Genetic screening prior to carbamazepine prescription is essential especially in susceptible populations.